2005
DOI: 10.1080/13668800500262752
|View full text |Cite
|
Sign up to set email alerts
|

Economic Roulette

Abstract: When is a job not a job?Complementing previous literature on welfare reform and the character of jobs in the lowwage labour market, we illustrate the lack of regularity and security that mark the jobs held by many low-income mothers. To do so, we present a typology of mothers' work patterns and illustrate their experiences through case examples. Our qualitative analysis of longitudinal pathways-to-work in three cities involved an examination of the experiences of 99 diverse, low-income working mothers with a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The coefficient of variation is commonly used in research on this topic (Rodems and Shaefer, 2020). Second, given qualitative research showing the difficulty mothers face seeking to approximate full-time work by piecing together multiple jobs (Lein et al, 2005), I include a variable assessing whether the mother worked multiple jobs simultaneously during the reference month. Third, Food Insecurity in Employed Lone Mother Households involuntary part-time work measures whether or not a respondent worked part-time due to either not being able to find a full-time job or due to slack work or material shortage at sometime during the Wave.…”
Section: Food Insecuritymentioning
confidence: 99%
See 3 more Smart Citations
“…The coefficient of variation is commonly used in research on this topic (Rodems and Shaefer, 2020). Second, given qualitative research showing the difficulty mothers face seeking to approximate full-time work by piecing together multiple jobs (Lein et al, 2005), I include a variable assessing whether the mother worked multiple jobs simultaneously during the reference month. Third, Food Insecurity in Employed Lone Mother Households involuntary part-time work measures whether or not a respondent worked part-time due to either not being able to find a full-time job or due to slack work or material shortage at sometime during the Wave.…”
Section: Food Insecuritymentioning
confidence: 99%
“…Third, Food Insecurity in Employed Lone Mother Households involuntary part-time work measures whether or not a respondent worked part-time due to either not being able to find a full-time job or due to slack work or material shortage at sometime during the Wave. Qualitative studies suggested that mothers with inadequate hours or wages will be engaged in constant job search at the same time they are working (Lein et al, 2005), which will again limit the time and energy needed to provide food for their families. Last, I also construct a variable measuring whether or not a mother experienced at least one period of job loss in the past year.…”
Section: Food Insecuritymentioning
confidence: 99%
See 2 more Smart Citations